Feasibility of Applying the Life History Calendar in a Population of Chronic Opioid Users to Identify Patterns of Drug Use and Addiction Treatment. (January 2014) - Fikowski, Jill; Marchand, Kirsten; Palis, Heather; Oviedo-Joekes, Eugenia
Uncovering patterns of drug use and treatment access is essential to improving treatment for opioid dependence. The life history calendar (LHC) could be a valuable instrument for capturing time-sensitive data on lifetime patterns of drug use and addiction treatment. This study describes the methodology applied when collecting data using the LHC in a sample of individuals with long-term opioid dependence and aims to identify specific factors that impact the feasibility of administering the LHC interview. In this study, the LHC allowed important events such as births, intimate relationships, housing, or incarcerations to become reference points for recalling details surrounding drug use and treatment access. The paper concludes that the administration of the LHC was a resource-intensive process and required special attention to interviewer training and experience with the study population. These factors should be considered and integrated into study plans by researchers using the LHC in addiction research.